Electrodeposition of Si in Molten LiF-NaF-KF Mixed with Various Sized SiO2 Particles. (25th October 2017) - Suzuki, Yuta; Yokota, Masayuki; Sakanaka, Yoshihide; Fukunaka, Yasuhiro; Goto, Takuya
Abstract : Si was electrodeposited potentiostatically on Ag substrates in molten LiF-NaF-KF mixed with various sized SiO2 particles at 873 K for 0.30-45 C cm -2 . The electrodeposition mechanism of Si was focused on the addition of various sized SiO2 particles as starting materials: the average particles size of which were ca. 9.1 µm and ca. 0.80 µm. The cyclic voltammograms indicated that the dissolution rate or behavior of SiO2 in molten salt changed with the particles size of SiO2 powders. For using large sized SiO2 particles, growth process of dense c-Si film was observed, although the morphology of electrodeposited Si was rough for using small sized SiO2 .